Advances in enterprise engineering X : 6th Enterprise Engineering Working Conference, EEWC 2016, Funchal, Madeira Island, Portugal, May 30 - June 3, 2016, Proceedings /: 6th Enterprise Engineering Working Conference, EEWC 2016, Funchal, Madeira Island, Portugal, May 30 - June 3, 2016, Proceedings. (2016) - Unknown
No abstract available